«Dragons» and «Chimeras» of Hybrid Wars - A. Dimitrovska (Vestnik MGIMO-Universiteta)
Abstract: Review of the book by Egorchenkov D.A., Danyuk N.S. Hybrid Dragon and Chimera of War. Мoscow, UNITY-DANA Publ., 2019. 367 p. (in Russian)